The EVALUASI IMPLEMENTASI PROGRAM PEMBELAJARAN BAHASA INGGRIS DI SMA KEPULAUAN KANGEAN KABUPATEN SUMENEP - Aini, Siti Hairatul; Eko Handoyo; Wiwi Isnaeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The success of the learning process in the classroom is determined by the extent to which the learning activities carried out by teachers and students in the classroom can achieve learning objectives. The English language proficiency of high school students is still in the poor category. This shows that the implementation of the current English language learning program is not yet fully effective in achieving the expected educational goals. Therefore, it is very important to evaluate the implementation of the English language learning program. This study is an evaluation study using a mixed method (quantitative and qualitative) approach with the CIPP model to determine the extent of the quality of the learning process and English learning curriculum in schools as well as external factors that influence it. Data collection techniques were carried out through the distribution of questionnaires, learning observations, and interviews. The research results on the context component show that students feel that English language skills are very important to support their future careers, so English language learning in the classroom must be tailored to students' needs to improve their competencies (M = 3.62 and 3.25), such as vocabulary learning and more frequent practice in speaking English. All students at Arjasa State High School and Muhammadiyah 3 Arjasa High School are from the Kangean Islands in Sumenep Regency. The economic background of the students' parents was assessed based on their occupations, with 15% being entrepreneurs, 25% farmers, 40% migrant workers, and 20% having no regular income. The recommendation based on the results of this study is to implement activities to improve the competence of English teachers, especially PPG and MGMP, as well as adequate infrastructure and facilities.